A splash of soy : everyday food from Asia - Lee, Lara (Chef) (Bloomsbury Publishing, 2023)
"Named after the simplicity and usefulness of soy, Lara Lee's new cookbook introduces 80 game-changing recipes that close the gap between classic Asian dishes and quick-to-table family meals. There are recipes that only require a little chopping and a boiled kettle, as well as 15, 30, and 45 minute meals fit for weeknight dinners or no-fuss dinner parties"--